Augmentation of Innate Host Defense by Expression of a Cathelicidin Antimicrobial Peptide - Bals, Robert (American Society for Microbiology, 1999)
Antimicrobial peptides, such as defensins or cathelicidins, are effector substances of the innate immune system and are thought to have antimicrobial properties that contribute to host defense. The evidence that vertebrate antimicrobial peptides contribute to innate immunity in vivo is based on their expression pattern and in vitro activity against microorganisms. The goal of this study was to investigate whether the overexpression of an antimicrobial peptide results in augmented protection against bacterial infection. C57BL/6 mice were given an adenovirus vector containing the cDNA for LL-37/hCAP-18, a human cathelicidin antimicrobial peptide. Mice treated with intratracheal LL-37/hCAP-18 vector had a lower bacterial load and a smaller inflammatory response than did untreated mice following pulmonary challenge with Pseudomonas aeruginosa PAO1. Systemic expression of LL-37/hCAP-18 after intravenous injection of recombinant adenovirus resulted in improved survival rates following intravenous injection of lipopolysaccharide with galactosamine or Escherichia coli CP9. In conclusion, the data demonstrate that expression of an antimicrobial peptide by gene transfer results in augmentation of the innate immune response, providing support for the hypothesis that vertebrate antimicrobial peptides protect against microorganisms in vivo.